Kepemimpinan yang profesional menjadi kunci sukses dalam pendidikan AUD di era modern - Illun Muallifah; Zahwa Rahman; Rahma Kamila; Lia Farikhatus; Fathimatul Husna (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2026)
Early Childhood Education (PAUD) plays a crucial role as a foundation for child development, but its success in the modern era is greatly influenced by the quality of principal leadership. This study aims to examine the role of principals' professional leadership in building a learning environment that balances conventional methods and the integration of digital technology, and how this leadership improves the overall quality of the institution. Using a descriptive qualitative approach, data were obtained through participant observation, in-depth interviews with principals, teachers, and parents, and document analysis (RKT and BOP). The research findings indicate that responsive, insightful, and transformative professional leadership is a key factor in PAUD management. Competent principals can formulate an adaptive vision, incorporate technology as a supporting tool while still emphasizing face-to-face interactions, and manage resources transparently and responsibly. Furthermore, a culture of collaboration and support for teacher development has been shown to enhance innovation in learning. The study concludes that professional leadership focused on human resource development and lifelong learning significantly influences the optimization of child development amidst socio-economic changes and technological advancements.